Apakah sustainability report dan political connection mempengaruhi nilai perusahaan - Putri, Meyda; Hardiningsih, Pancawati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Optimizing industry numbers means maximizing shareholder abundance as an important industrial goal, because industry numbers are believed to be able to determine the direction and strength of the industry's operating capital in the future. The purpose of this research is to try the results of sustainability reports and political connections to industry figures. The research population is the manufacturing industry in the factory zone listed on the Indonesian Impact Money Market for 2018-2020. The illustration is filtered using the purposive sampling method with the standard of having all the information and publishing the sustainability report needed in this research. The 3 time spans of the cross-sectional poll are a total of 63 industries. The information analysis method in this research uses Multiple Linear Regression. The research results prove that there is no effect of the sustainability report on economic capacity to industry figures. There are important positive consequences of the sustainability report on social capabilities, area capabilities, and political connections to industry figures.